2006
DOI: 10.1016/j.devcel.2006.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Decapping Protein 1, dDcp1, Is a Component of the oskar mRNP Complex and Directs Its Posterior Localization in the Oocyte

Abstract: In Drosophila, posterior deposition of oskar (osk) mRNA in oocytes is critical for both pole cell and abdomen formation. Exon junction complex components, translational regulation factors, and other proteins form an RNP complex that is essential for directing osk mRNA to the posterior of the oocyte. Until now, it has not been clear whether the mRNA degradation machinery is involved in regulating osk mRNA deposition. Here we show that Drosophila decapping protein 1, dDcp1, is a posterior group gene required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(120 citation statements)
references
References 62 publications
(89 reference statements)
6
114
0
Order By: Relevance
“…3B). Staining of Dnmt2 genTG-EGFP ovaries with an antibody to ME31B, a Drosophila RNA processing body component in the germline (Lin et al 2006), also showed processing body signals after heat shock with strong colocalization of Dnmt2 and ME31B (Fig. 3C).…”
Section: Resultsmentioning
confidence: 88%
“…3B). Staining of Dnmt2 genTG-EGFP ovaries with an antibody to ME31B, a Drosophila RNA processing body component in the germline (Lin et al 2006), also showed processing body signals after heat shock with strong colocalization of Dnmt2 and ME31B (Fig. 3C).…”
Section: Resultsmentioning
confidence: 88%
“…Second, the Argonaute I homolog from sea urchins, Seawi, has been identified as a microtubule-associated protein and localizes in cytoplasmic puncta (Rodriguez et al 2005). Third, the oskar mRNP in Drosophilia oocytes, which contains several P-body proteins, mislocalizes in mutants in which microtubule organization is abnormal (Lin et al 2006). While a precise function for P-bodies in mRNA metabolism remains ambiguous, taken together, these results suggest that P-bodies and similar mRNP granular structures are influenced by the microtubule network in the cell, and P-body assembly is not obligatorily dependent on global alterations in mRNA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mRNA decay blocks could also affect germ granules and neuronal transport granules, with which P-bodies also physically interact. 14,15 Notably, various mRNA degradative enzymes are found in mRNP granules besides P-bodies, such as Xrn1 in stress granules 11 and Drosophila/mouse spermatid nuage, 65 Dcp1/ Dcp2 in various germ granules, [66][67][68] and several Argonaute proteins with endonuclease activity in stress granules, 69 and various germ granules. [70][71][72][73] Whether mRNA degradation occurs in mRNP granules besides P-bodies remains poorly studied.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%